Knowledge Economy Readiness, Innovativeness and Competitiveness of the Western Balkan Countries - Cvetanović, Slobodan; Ilić, Vojislav; Despotovic, Danijela; Nedić, Vladimir (Industrija, 2015)
The Western Balkan countries have set themselves the goal to join the European Union as soon as possible. Accordingly, they must adjust the key components of their development policies to the strategy Europe 2020, whose key priorities are reflected in smart sustainable and inclusive growth. This paper explores the relationship among knowledge economy readiness, innovativeness, and competitiveness of six Western Balkan countries (Albania, Bosnia and Herzegovina, Macedonia, Serbia, Croatia, and Montenegro) and the group of six selected neighboring EU countries (Austria, Bulgaria, Greece, Hungary, Romania, and Slovenia). The paper relies on the data obtained from the Knowledge Economy Index of the World Bank Institute, INSEAD’s Global Innovation Index and the Global Competitiveness Index of the World Economic Forum for 2013. The analysis of the interdependence of the aforementioned variables points to a statistically significant correlation between the indicator knowledge economy index and the global innovation index for both groups of countries. The analysis also indicates a statistically significant linear correlation between innovativeness and innovation efficiency ratio for the Western Balkan countries. Conversely, no respective correlation has been registered for the group of selected EU countries. Finally, no statistically significant correlation has been detected between the global innovation index and the global competitiveness index in the Western Balkan countries, while in respect of the group of selected EU countries, the existence of significant linear correlation between these variables has been revealed.
Keywords: Western Balkans; European Union; competitiveness; Innovation; knowledge